Associations between serum ghrelin and knee symptoms, joint structures and cartilage or bone biomarkers in patients with knee osteoarthritis. Issue 9 (September 2017) - Wu, J.; Wang, K.; Xu, J.; Ruan, G.; Zhu, Q.; Cai, J.; Ren, J.; Zheng, S.; Zhu, Z.; Otahal, P.; Ding, C.
Summary: Objective: The roles of ghrelin in knee osteoarthritis (OA) are unclear. This study aimed to examine cross-sectional associations of ghrelin with knee symptoms, joint structures and cartilage or bone biomarkers in patients with knee OA. Methods: This study included 146 patients with symptomatic knee OA. Serum levels of ghrelin and cartilage or bone biomarkers including cartilage oligomeric matrix protein (COMP), cross linked C-telopeptide of type I collagen (CTXI), cross linked N-telopeptide of type I collagen (NTXI), N-terminal procollagen III propeptide (PIIINP), and matrix metalloproteinase (MMP)-3, 10, 13 were measured using Enzyme-linked immunosorbent assay (ELISA). Knee symptoms were assessed using the Western Ontario and McMaster Universities Arthritis Index (WOMAC). Infrapatellar fat pad (IPFP) volume, IPFP signal intensity alternation, cartilage defects, bone marrow lesions (BMLs) and effusion-synovitis were assessed using the (MRI). Osteophytes and joint space narrowing (JSN) were assessed using the Osteoarthritis Research Society International atlas. Results: After adjustment for potential confounders, ghrelin quartiles were positively associated with knee symptoms including pain, stiffness, dysfunction and total score (quartile 4 vs 1: β 24.19, 95% CI 8.13–40.25). Ghrelin quartiles were also significantly associated with increased IPFP signal intensity alteration (quartile 4 vs 1: OR 3.57, 95% CI 1.55–8.25) and NTXI, PIIINP, MMP3 and MMP13. Ghrelin was not significantly associated with other joint structures and biomarkers. Conclusions: Serum levels of ghrelin were significantly associated with increased knee symptoms, IPFP signal intensity alteration and serum levels of MMP3, MMP13, NTXI and PIIINP, suggesting that ghrelin may have a role to play in knee OA.